When Do In-service Teacher Training and Books Improve Student Achievement? : Experimental Evidence from Mongolia - Fuje, Habtamu; Tandon, Prateek (World Bank, Washington, DC, 2015)
This study presents evidence from a randomized control trial (RCT) in Mongolia on the impact of in-service teacher training and books, both as separate educational inputs and as a package. The study tests for the complementarity of inputs and non-linearity of returns from investment in education as measured by students test scores in five subjects. It takes advantage of a national-scale RCT conducted under the Rural Education and Development project. The results suggest that the provision of books, in addition to teacher training, raises student achievement substantially. However, teacher training and books weakly improve test scores when provided individually. Students whose teachers have received training and whose classrooms have acquired books improved their cumulative score (totaled across five tests) by 34.9 percent of a standard deviation, relative to a control group. Students treated only with books improved their total score by 20.6 percent of a standard deviation relative to a control group of students. On the other hand, extra teacher training did not have a statistically significant effect on the total test score. In addition, providing both inputs jointly improved test scores in most subjects, which was not the case when either input was provided individually. This study sheds light on the relevance of supplementing teacher training schemes with appropriate teaching materials in resource-poor settings. The policy implication is that isolated education investments, in settings where complementary inputs are missing, could deliver minimal or no return.